2009
DOI: 10.1308/rcsann.2009.91.4.344b
|View full text |Cite
|
Sign up to set email alerts
|

Use of Portable Ultrasound for Exploration and Removal of Superficial Foreign Bodies

Abstract: Figure 1Swab rolled from apex and laid spirally after being soaked. It is then placed in the acetabulum cup to centralise the Explant device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…5,11,13,14 Common applications for portable ultrasound include evaluation for cardiac or abdominal abnormality. 5,14 The use of portable ultrasound in the musculoskeletal system has been described for foreign body removal 7,9 and rib fracture assessment. 12 One study evaluated 10 shoulders and concluded that abnormality could be identified 10 ; however, a comprehensive evaluation of routine musculoskeletal applications has not been previously assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,11,13,14 Common applications for portable ultrasound include evaluation for cardiac or abdominal abnormality. 5,14 The use of portable ultrasound in the musculoskeletal system has been described for foreign body removal 7,9 and rib fracture assessment. 12 One study evaluated 10 shoulders and concluded that abnormality could be identified 10 ; however, a comprehensive evaluation of routine musculoskeletal applications has not been previously assessed.…”
Section: Discussionmentioning
confidence: 99%
“…4 Such equipment has been used in several applications, such as trauma, cardiorespiratory assessment, and invasive procedures 4 ; however, the effectiveness of portable ultrasound in evaluation of the musculoskeletal system has not been fully assessed. 7,9,10,12 Thus, the purpose of this study was to evaluate the use of a portable hand-held ultrasound device in the evaluation of the musculoskeletal system compared with conventional cart-based ultrasound. The hypothesis was that portable hand-held ultrasound would be as effective as conventional cart-based ultrasound.…”
mentioning
confidence: 99%
“…In Abhängigkeit von der Erfahrung des Untersuchers und der Qualität des Ultraschallsystems kann der Fremdkörper schon ab einer Größe von 1-2 mm nachgewiesen werden[ 7 ] . Hinzu kommt die Einsatzmöglichkeit tragbarer Ultraschallgerä-te intraoperativ zur Lokalisation des Fremdkörpers ohne zusätz-liche Kosten oder zusätzlichen Personalaufwand[ 23 ] .Fremdkörper weisen in der Kopf-Hals-Sonografi e ein charakteristisches Echomuster auf und können daher, bis auf Lokalisationen hinter echodichten Strukturen wie Knochen, gut als solche identifi ziert werden. Die Darstellung mittels Sonografi e ist charakterisiert durch hohe Aufl ösung und die 3-dimensionale Mög-lichkeit der Darstellung, ist kostengünstig, nichtinvasiv und "vor Ort", sodass bei einem erfahrenen Untersucher oft keine zusätz-liche Bildgebung notwendig und eine zeitnahe (operative) Therapie möglich ist.…”
unclassified